2021
DOI: 10.3390/ani11041078
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Structure of Varanus komodoensis as Revealed by Computed-Tomographic Imaging

Abstract: This study aimed to describe the anatomic features of the normal head of the Komodo dragon (Varanus komodoensis) identified by computed tomography. CT images were obtained in two dragons using a helical CT scanner. All sections were displayed with a bone and soft tissue windows setting. Head reconstructed, and maximum intensity projection images were obtained to enhance bony structures. After CT imaging, the images were compared with other studies and reptile anatomy textbooks to facilitate the interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Modern diagnostic imaging techniques such as computed tomography and magnetic resonance imaging have revolutionised clinical diagnosis in reptile medicine since they are valuable tools that demonstrate appreciable advantages over conventional imaging techniques. Therefore, they make it possible to obtain views of body sections from various tomographic planes, providing images with an adequate anatomic resolution without the superimposition of the tissues, a high contrast between different structures, and excellent tissue differentiation [ 22 , 23 , 24 ]. Thus, advanced imaging technologies have improved the quality of anatomical imaging and diagnosis, enabling an exceptional evaluation of different anatomical regions and a better detection of different diseases such as metabolic bone disease, skull fractures, abscesses, and neoplasia [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern diagnostic imaging techniques such as computed tomography and magnetic resonance imaging have revolutionised clinical diagnosis in reptile medicine since they are valuable tools that demonstrate appreciable advantages over conventional imaging techniques. Therefore, they make it possible to obtain views of body sections from various tomographic planes, providing images with an adequate anatomic resolution without the superimposition of the tissues, a high contrast between different structures, and excellent tissue differentiation [ 22 , 23 , 24 ]. Thus, advanced imaging technologies have improved the quality of anatomical imaging and diagnosis, enabling an exceptional evaluation of different anatomical regions and a better detection of different diseases such as metabolic bone disease, skull fractures, abscesses, and neoplasia [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We should highlight that the evaluation of anatomic structures within the heads of loggerhead sea turtles and the examination of soft tissues is arduous because of the turtle’s anatomic difficulty [ 26 ]. Non-invasive imaging exams have already been performed to describe some structures of the eye in reptiles, such as the Komodo dragon [ 23 , 24 ], the green iguana, the common tegu, and the bearded dragon [ 25 ], and different species of turtles inhabiting marine, freshwater, and terrestrial environments such as the green turtle, the black-bellied slider, the loggerhead turtle, and the red-footed tortoise [ 21 , 26 ]. Different studies have used contrast media to enhance the densities of both humours [ 19 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, the anatomy of different reptile species has already been thoroughly described employing diagnostic imaging techniques [ 13 , 14 , 15 ]. Authors have reported atlases of green, loggerhead and leatherback sea turtles [ 15 , 16 , 17 , 18 ], komodo dragons [ 19 , 20 ] and green iguanas [ 12 , 15 , 21 , 22 ], snakes and lizards [ 21 ]. Concerning the rhinoceros iguana, most of the studies are focused on population genetics [ 23 ], evolution and historical biogeography [ 24 ], and on some pathologic descriptions such as osteopetrosis-like conditions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moving from mammals to reptiles, this Special Issue contains a study of the head of the monitor lizard by Pérez et al [ 13 ], which includes advanced imaging techniques, such as CT and 3D head reconstruction in order to explore the complex anatomy of the head and associated structures of these animals. They used sagittal and transverse CT images, volume-rendered reconstructed CT images, as well as maximum intensity projection (MIP) images to map the head of the Komodo dragon.…”
mentioning
confidence: 99%